Designing effective STEM courses: a mixed-methods study of the impact of a STEM education course on teachers’ self-efficacy and course experiences - Zhumabay, Nurman; Yelemessova, Zhaudir; Balta, Nuri; Abylkassymova, Alma; Bakytkazy, Tannur; Marynowski, Richelle (Frontiers in Education, 2024)
Science, Technology, Engineering, and Mathematics (STEM) fields play a critical role in the advancement of society and are expected to grow rapidly in the coming years. This study examines the development of a STEM education course and its impact on teachers’ self-efficacy and course experiences. The study involves a mixed-methods approach, using survey and course assignment results gathered from 52 mathematics master’s degree candidates who took an online STEM education course. Teachers’ self-efficacy, STEM knowledge, reflections from reading materials, and lesson plans were quantitively analyzed while content analyses was employed for the teachers’ opinions on the role of each STEM subject and overall course evaluation. Results showed a significant increase in teachers' self-efficacy in teaching STEM subjects after completing the course. Additionally, teachers reported positive experiences related to course content, activities, and assignments. The study provides insights into the design and implementation of effective STEM courses and provides practical implications for designing operative STEM courses.